The Impact of Ethnomathematics Approach on Numeracy and Mathematical Reasoning Skills of Elementary School Students: A Systematic Literature Review - Nia Diyawati Utami; Neni Mariana; Rooselyna Ekawati (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2026)
This systematic literature review examines the effects of ethnomathematics-based approaches on numeracy and mathematical reasoning skills among elementary school students. The review analyzed 18 empirical studies and meta-analyses published between 2022 and 2025 to capture recent evidence aligned with contemporary educational contexts and pedagogical practices. Using PRISMA guidelines, quantitative and qualitative findings from quasi-experimental, mixed-method, and meta-analytic studies were synthesized. This review addresses a notable research gap, as recent literature has not comprehensively examined the combined impact of ethnomathematics on both numeracy and mathematical reasoning at the elementary level. The findings consistently demonstrate that ethnomathematics-based instruction significantly improves students’ numeracy achievement and mathematical reasoning abilities. Meta-analytic results indicate strong to very strong effect sizes (ES = 1.22–1.42) on mathematical achievement. Culturally contextualized learning also enhances conceptual understanding, critical thinking, collaboration skills, and learning motivation. Positive effects are reported across grade levels and cultural contexts, with moderate to high improvements in numeracy outcomes. Various implementation modalities, including interactive digital media, traditional games, STEAM-oriented instruction, and culturally relevant learning modules, show high instructional validity and effectiveness. However, several studies exhibit methodological limitations, such as small sample sizes, limited use of control groups, and insufficient longitudinal analysis. Future research should prioritize large-scale and longitudinal studies, alongside systematic teacher professional development, to support the sustainable integration of ethnomathematics in elementary mathematics education.